Evaluation of General Dentists' Attitude in Sanandaj Regarding Antibiotic Prescription in Root Canal Treatment and Related Factors - H Akhavan; S Tour savadkouhi; N Emami; H labaf ghasemi; GH Anoosh; A Zareyi; SS Seyed salehi (Islamic Azad University, 2019)
Background and Aim: One of the main concerns in dental society is the enormous prescription of antibiotics. Unnecessary prescription of antibiotics causes resistant bacterial species. The aim of this study was to evaluate the attitude of dentists toward antibiotic prescription in endodontic treatments and the role of related factors. The study was conducted in Sanandaj city, Kurdistan province, Iran, in 2017. Materials and Methods: This quantitative cross-sectional study involved active dentists in Sanandaj city. Their attitude toward antibiotic prescription was evaluated using 20 questions (10 in favor of prescribing antibiotics and 10 against it) with the following options: "totally agree, agree, disagree, and totally disagree". The role of related factors including age, sex, work experience, level of interest in endodontic treatments, and the number of endodontic cases, were analyzed by Chi-square test. Results: The study was conducted on 145 dentists (72.5% males and 27.5% females) in Sanandaj city. The mean age of the participants was 39±11 years, and their mean work experience was 13±8 years. 7.5±0.9% of the dentists chose the "totally agree" option, and 92.5±1.1% of them chose the "agree" option regarding antibiotic prescription in endodontic treatments. Conclusion: It seems that the positive attitude towards antibiotic prescription in endodontic treatments was satisfactory among the studied dentists.